Structural modifications and kinetic effects of KRAS interactions with HRAS and NRAS: an in silico comparative analysis of KRAS mutants - Silverman, Isaac; Gerber, Michael; Shaykevich, Aaron; Stein, Yitzchak; Siegman, Alexander; Goel, Sanjay; Maitra, Radhashree (Frontiers in Molecular Biosciences, 2024)
The RAS genes which code for KRAS, HRAS, and NRAS are three of the most frequently mutated oncogenes responsible for cancer deaths. Tumorigenesis is one of the most significant outcomes of deregulation of the RAS GTPases. Although the structures have been extensively studied, there is still more to be discovered about the actual binding conformations of the three isoforms, especially when mutated, to design an inhibitory drug. Recent studies have identified important interactions between the three isoforms that affect the oncogenic strength of the others when they are mutated. In this study, we utilize molecular dynamics simulations to examine the modifications of the structural property, mechanism, and kinetic energy of KRAS when interacting individually and with HRAS and NRAS. Notably, we found that WT-KRAS' orientation when bound to WT-HRAS vs. WT-NRAS is rotated 180º, with mutants demonstrating a similar binding pattern. The binding sites of the isoforms with KRAS share similarities with those involved in the GDP/GTP active site and site of KRAS dimerization. Thus, isoform interaction can serve as an inhibitory method of KRAS actions. This study advances the understanding of inhibiting RAS-driven cancers through a novel isoform interaction approach only recently discovered, which has been proven to be an effective alternate therapeutic approach. We developed a blueprint of the interaction which would be beneficial in the development of KRAS mutant specific and pan-KRAS mutant inhibitory drugs that mimic the isoform interactions. Our results support the direct interaction inhibition mechanism of mutant KRAS when bound to WT-HRAS and WT-NRAS by the isoforms' hypervariable region binding to the G-domain of KRAS. Furthermore, our results support the approach of reducing the effects of oncogenic KRAS by altering the concentration of the isoforms or a drug alternative based on the overall structural and kinetic stability as well as the binding strength of the mutant-isoform complexes.